2016
DOI: 10.1055/s-0036-1588342
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Enantioselective Oxidative α-C–H Functionalization of Amines

Abstract: Cross-dehydrogenative coupling (CDC) has emerged as a powerful synthetic method for the straightforward and efficient construction of C-C and C-heteroatom bonds. In particular, asymmetric versions of this reaction are highly desirable, since they would provide a simple approach to complex molecules from simple materials without any prefunctionalization of substrates. In recent years, great achievements have been made in this area, and many powerful approaches have been developed for this transformation with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26] Despite the great advances in the field of CDC reactions over the last two decades, most of the early studies have focused on nonasymmetric transformations. [4][5][6][7][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] However, enantioselective CDC reactions have been relatively less developed, [36][37][38][39][40][41][42] and achieving high levels of enantioselectivity in these reactions is the primary challenge. The first report of a catalytic enantioselective CDC reaction dates back to 2004 when Li and co-workers demonstrated that a chiral copper complex could catalyze the enantioselective CDC reaction of N-aryl tetrahydroisoquinolines (THIQs) with alkynes.…”
Section: Jie Luomentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25][26] Despite the great advances in the field of CDC reactions over the last two decades, most of the early studies have focused on nonasymmetric transformations. [4][5][6][7][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] However, enantioselective CDC reactions have been relatively less developed, [36][37][38][39][40][41][42] and achieving high levels of enantioselectivity in these reactions is the primary challenge. The first report of a catalytic enantioselective CDC reaction dates back to 2004 when Li and co-workers demonstrated that a chiral copper complex could catalyze the enantioselective CDC reaction of N-aryl tetrahydroisoquinolines (THIQs) with alkynes.…”
Section: Jie Luomentioning
confidence: 99%
“…43 Since then, different chiral metal catalysts have been developed to realize various enantioselective CDC reactions. [36][37][38][39][40][41][42] Compared to metal catalysis, [44][45][46] organocatalysis [47][48][49][50][51][52] offers distinct advantages such as nonmetallic nature, mild reaction conditions, enhanced compatibility between catalysts and oxidants, and different activation modes and so on. [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] This methodology has also found application in enantioselective CDC reactions.…”
Section: Jie Luomentioning
confidence: 99%
“…3 In contrast to a sulfone, the sulfoximine group has an additional site that could be functionalized at the NH bond. Introduction of groups such as trifluoromethyl, 6 h alkyl, 6 c , s acyl, 6 d , r alkynyl, 6 j , l – n allyl, 6 k alkenyl, 6 p , q sulfenyl, 6 b phosporyl, 6 a silyl, 6 f cyano, 6 g , o aryl 7 and heteroaryl 8 at the nitrogen atom of sulfoximine has been well documented in the sulfoximine literature. 6–8 Among these, the synthesis of N -arylsulfoximines has attracted a wider attention.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of groups such as trifluoromethyl, 6 h alkyl, 6 c , s acyl, 6 d , r alkynyl, 6 j , l – n allyl, 6 k alkenyl, 6 p , q sulfenyl, 6 b phosporyl, 6 a silyl, 6 f cyano, 6 g , o aryl 7 and heteroaryl 8 at the nitrogen atom of sulfoximine has been well documented in the sulfoximine literature. 6–8 Among these, the synthesis of N -arylsulfoximines has attracted a wider attention. There are relatively fewer reports that describe the synthesis of N -heteroaryl sulfoximines despite their potential utility in medicinal chemistry 3,9 and agro applications.…”
Section: Introductionmentioning
confidence: 99%
“…6 In recent years, various increasing efforts have been made for the explosive development of the α-functionalization of amines. 7 However, the direct β-C–H functionalization of amines has been less explored owing to the distal bonds being less electron-rich. 8 Regrettably, the achievements in the directed β-C–H functionalization of amines mostly involve an enamine intermediate generated under oxidative conditions that require the use of transition metals or stoichiometric amounts of oxidants (Scheme 1a).…”
mentioning
confidence: 99%